1975
DOI: 10.1136/jcp.28.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Haematological changes in active chronic hepatitis with reference to the role of the spleen.

Abstract: The haematological role of the spleen has been investigated in a series of 22 patients with active chronic hepatitis. Severe pancytopenia occurred in one patient after three years of steroid therapy and this episode was associated with an increase in spleen size and a high splenic index of red cell destruction. Although the spleen was usually enlarged in the remainder of treated and untreated patients no others showed increased splenic haemolysis. The red cell survival was slightly reduced in most patients but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…How much this effect is responsible for the encouraging rise in platelet count after splenectomy in active chronic hepatitis (Boye et al, 1972) is uncertain. Undoubtedly in some patients with active chronic hepatitis the thrombocytopenia may be part of an 'immune crisis' (Toghill and Green, 1975), and although the role of splenectomy in these circumstances is speculative some results have been heartening (Fodor and Barbarino, 1972). Reducing portal pressure may be important in improving platelet survival, as was the case with our patient (Case 11) after a splenorenal shunt and in other patients with portocaval shunting (Castaldi and Firkin, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…How much this effect is responsible for the encouraging rise in platelet count after splenectomy in active chronic hepatitis (Boye et al, 1972) is uncertain. Undoubtedly in some patients with active chronic hepatitis the thrombocytopenia may be part of an 'immune crisis' (Toghill and Green, 1975), and although the role of splenectomy in these circumstances is speculative some results have been heartening (Fodor and Barbarino, 1972). Reducing portal pressure may be important in improving platelet survival, as was the case with our patient (Case 11) after a splenorenal shunt and in other patients with portocaval shunting (Castaldi and Firkin, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of red cell mass (RCM), splenic red cell pool (SRCP), red cell survival (RCS) and surface counting studies were also carried out in Cases 3, 4, 7, 8, 9 and 11, using "Cr-labelled erythrocytes as described earlier (Toghill and Green, 1975). Plasma volumes (PV) were measured using lZ5I-or 1311-labelled human albumin.…”
Section: Methodsmentioning
confidence: 99%
“…The low platelet count is commonly independent of the cause of liver disease, but it seems to be related to the degree of liver failure [3]. The mechanism of thrombocytopenia has been attributed mainly to hypersplenism [4,5], although other factors such as reduced mean life span with increased platelet turnover have also been demonstrated [6-81. The key role played by the spleen has been challenged by studies showing no relation between the low platelet count and the presence of splenomegaly [9] and by the observations that surgical procedures such as portocaval shunts do not usually normalize the platelet count [ 101. However, recent kinetics studies have shown that the sequestration of platelets by the spleen is a prominent feature in patients with CLD [8,11], but it is still uncertain whether the platelets are removed as a result of the spleen function or due to an intrinsic damage of the platelets, specifically, at the level of the platelet membrane.…”
Section: Introductionmentioning
confidence: 99%